Retrospective analysis of dental implant failure rates in patients with compromised health - Sourav C Bidyasagar Bal; Vaibhav N Awinashe; Pankaj Jindal; Anas Abdul Khader; Faris J Almutairi; Anuj Singh Parihar; Vardarajula V Ramaiah (Wolters Kluwer Medknow Publications, 2023)
Objectives: The goal of the current research was to compare the failure rate of dental implants in medically compromised patients to healthy individuals. Materials and Methods: In this seven years retrospective study, 50 patients from Group A who were medically compromised had 63 implants, while 50 patients from Group B who were healthy had 67 implants. Over 1 mm of bone loss around the implant in the first year and over 0.2 mm of bone loss per year after that were considered failure rates. Result: Two (2.9%) of the dental implants in Group B and 18 (28.6%) in Group A, both failed. The average bone loss around the implant in Group A during the first year was 1.21 mm, compared to 0.3 mm in Group B. Conclusion: Uncontrolled diabetes mellitus group had greater implant failure.